Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00345-014-1327-0
|View full text |Cite
|
Sign up to set email alerts
|

Update on the use of diode laser in the management of benign prostate obstruction in 2014

Abstract: More randomized controlled studies are needed to determine the position and the ideal technique of diode laser treatment for BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…
followed in 2004 [2], then later in the end of the 2000s all other transurethral laser-based enucleation techniques: Tm:YAG Vapoenucleation (ThuVEP) [3], transurethral anatomical enucleation with Tm:YAG Support (ThuLEP) [4], diode laser enucleation of the prostate (DiLEP) [5] and finally Lithium-Borate "Greenlight" enucleation of the prostate (GreenLEP) [6] appeared on the market to finally replace open prostatectomy (OP) and TURP. It took Thulium:YAG as the challenger to initiate a discussion about the impact of laser in transurethral enucleation.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
followed in 2004 [2], then later in the end of the 2000s all other transurethral laser-based enucleation techniques: Tm:YAG Vapoenucleation (ThuVEP) [3], transurethral anatomical enucleation with Tm:YAG Support (ThuLEP) [4], diode laser enucleation of the prostate (DiLEP) [5] and finally Lithium-Borate "Greenlight" enucleation of the prostate (GreenLEP) [6] appeared on the market to finally replace open prostatectomy (OP) and TURP. It took Thulium:YAG as the challenger to initiate a discussion about the impact of laser in transurethral enucleation.
…”
mentioning
confidence: 99%
“…ThuVEP focuses on the favorable vaporization effect of continuous-wave lasers to perform a fast, effective and safe enucleation, whereas ThuLEP focuses on almost blunt mechanical enucleation using the laser only for dissection of adherences and mucosa. The latter on anatomy focusing approach was mimicked by other continuous-wave lasers (LBO/"Greenlight" and 980 nm diode laser) that had not been found suitable for enucleation at the initial point of the discussion [5,6].…”
mentioning
confidence: 99%
“…Transient stress urinary incontinence is often encountered after endosurgery for prostate enucleation, and was found in 3.3%–7.5% cases after DiLEP. 24 This study demonstrated that DiLEP occurrence was 6.6%, compared with 3.9% in the PKRP group ( P = 0.468), similar to HoLEP and thulium laser vaporization enucleation of the prostate (ThuVEP). 25,26 Stress urinary incontinence disappeared at 3 months postoperatively by exercising the levator ani muscle.…”
Section: Discussionmentioning
confidence: 57%
“…TUERP combined with the concept of conventional open surgery and transurethral resection of the prostate, can not only completely remove the gland but can also reduce bleeding; it is less invasive to the body and has been recognized by clinical experts [29]. Although the energies used for enucleation of the prostate by urologists may be different, such as holmium laser [30], thulium laser [31], diode laser [32], or plasma kinetic energy [14,33], the principle is similar which include identification of the tissue plane between the adenoma and the surgical capsule, and anatomical enucleation of the adenoma, and this technique has the advantage of being an extravesical procedure, better controlling the bleeding and avoiding bladder incision. TUERP can reduce wound repair time, thus shortening bladder irrigation time, catheterization time, and postoperative hospital stay [12,34].…”
Section: Discussionmentioning
confidence: 99%